2015
DOI: 10.2174/1874079001508010001
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Consumption and Oral, Pharyngeal and Lung Cancers

Abstract: Tobacco consumption remains a significant threat to public health around the world and smoking-related diseases are considered the world's most preventable cause of death. Smoking is associated to several diseases and conditions, most importantly different types of cancer. At least 30% of all cancer death is related to smoking including 87% and 70% of lung cancer deaths in men and women, respectively. Lung cancer is the leading cause of cancer deaths compared to cancer of other organs in both men and women. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…It is clear that cancer is an urgent global challenge that need prevention, early detection and diagnosis, treatment, and care services. Meanwhile tobacco consumption also remains a significant threat to public health and associated with different types of cancer (Bassiony et al, 2015;Islami et al, 2015). This study found that tobacco smoking was responsible for 121,849 new cancer cases in 2018 (106,858 male and 14,991 female cases) in ASEAN 2018.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is clear that cancer is an urgent global challenge that need prevention, early detection and diagnosis, treatment, and care services. Meanwhile tobacco consumption also remains a significant threat to public health and associated with different types of cancer (Bassiony et al, 2015;Islami et al, 2015). This study found that tobacco smoking was responsible for 121,849 new cancer cases in 2018 (106,858 male and 14,991 female cases) in ASEAN 2018.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking increases the risk of malignant tumors in nearly all organs with at least 30% of all cancer deaths smoking is attributed to smoking (Bassiony et al, 2015). Once tobacco has damaged cells, they can grow uncontrollably as cancer.…”
Section: Introductionmentioning
confidence: 99%
“…As some of the chemicals of tobacco are carcinogenic, the consumption of tobacco has been associated with many forms of cancer. 33,[43][44][45][46][47] In fact, almost all known cancers can be correlated to tobacco consumption. However, the most direct involvement of cancer can be seen in cancer of the mouth, lungs, esophagus, stomach, liver, pharynx, colon, etc.…”
Section: Tobacco and Cancermentioning
confidence: 99%
“…It creates the highest rate of mortality and morbidity in India, where this carcinoma form records for 40% of all malignant tumors (Bagan et al, 2010). Any form of tobacco with alcohol intake is known as the major risk factor for the higher incidence of oral cancer in India (Bassiony et al, 2015). DMBA induced an experimental animal model for evaluating the chemoprevention study of oral cancer (Manoharan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%